A corrosion-resistant nickel-aluminum intermetallic compound coating and a method for preparing the same

CN122979706APending Publication Date: 2026-10-27珠海城市职业技术学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611046623.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

热喷涂(等离子喷涂、电弧喷涂、火焰喷涂)应用最广,效率高、成本适中,但涂层孔隙率较高、结合强度有限;扩散渗镀(包埋渗铝、料浆渗铝)工艺成熟、结合力强,适合复杂构件,但温度高、周期长、成分控制难度大

Benefits of technology

1、本发明采用高纯氩气密闭环境与无水乙醇作为过程控制剂、间歇式球磨工艺,依靠磨球机械挤压使软铝均匀包覆镍颗粒,规避常规混粉工艺镍铝粉体混杂、局部铝富集或缺铝缺陷;乙醇有效抑制粉体冷焊团聚,配合梯度筛分,核壳包覆完整度≥95%,本发明基于规整核壳结构,最终粉末杂相总含量<3wt%,单Ni3Al纯度>97%;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979706A_ABST
    Figure CN122979706A_ABST
Patent Text Reader

Abstract

The application provides a kind of corrosion-resistant nickel-aluminum intermetallic compound coating and its preparation method, the coating is composed of single-phase Ni3Al intermetallic compound and 1% Al2O3 dispersed particles of the total mass of single-phase Ni3Al intermetallic compound.The application has high density, excellent salt spray resistance and high-temperature oxidation resistance, the application precisely controls the ratio of nickel and aluminum by core-shell coating, inhibits the generation of heterogeneous phase by segmented heat treatment, avoids substrate high-temperature deformation and grain coarsening by cold spraying low-temperature forming, and Al2O3 dispersion strengthening further improves the coating density and corrosion resistance;Compared with traditional thermal spraying and plating process, the coating has low porosity, strong bonding force, excellent thermal shock stability, controllable preparation process, moderate production cost, and can be used in large scale for aerospace hot end components, petrochemical carbon steel equipment corrosion protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating materials technology, and in particular to a corrosion-resistant nickel-aluminum intermetallic compound coating and its preparation method. Background Technology

[0002] Existing technologies for preparing nickel-aluminum composite coatings have formed a diverse system, primarily based on thermal spraying, diffusion plating, vapor deposition, electroplating / chemical plating, and laser cladding, supplemented by cold spraying, induction heating, and composite processes. Each method differs significantly in cost, efficiency, coating quality, and applicable scenarios. Thermal spraying (plasma spraying, arc spraying, flame spraying) is the most widely used, offering high efficiency and moderate cost, but its coating porosity is relatively high, resulting in limited bonding strength. Diffusion plating (embedding aluminizing, slurry aluminizing) is a mature process with strong adhesion, suitable for complex components, but it involves high temperatures, long cycles, and difficulty in controlling composition. Chemical vapor deposition (CVD) can prepare dense and uniform coatings, adapting to complex surfaces, but it suffers from expensive equipment, stringent atmosphere control, and environmental risks. Electroplating / chemical plating equipment is simple and low-cost, easily producing thin and gradient coatings, but it generates significant pollution, and thick coatings have a high risk of stress and cracking. Laser cladding offers concentrated energy, low dilution rate, and controllable microstructure, enabling the production of dense and strongly bonded coatings. However, it suffers from high equipment costs and low efficiency in large-area production. Cold spraying is environmentally friendly and efficient, with no oxidation phase transition, making it suitable for coatings with high aluminum content. However, it suffers from insufficient density and poor spraying controllability.

[0003] Currently, various nickel-aluminum composite coating preparation technologies still have many shortcomings: thermal spray coatings generally have many porosity defects and low density, making them susceptible to media penetration and corrosion under high-temperature service, and their insufficient interfacial bonding strength leads to peeling. Infiltration plating processes require high preparation temperatures, easily causing coarse substrate grains and component deformation, and the coating thickness uniformity is poor, making it difficult to precisely control the nickel-aluminum element ratio. Vapor deposition methods require large equipment investment and have low preparation efficiency, making it difficult to achieve mass industrial production of large components. Electroplating and electroless plating involve wastewater pollution, thick coatings have high internal stress and are prone to cracking, and have poor high-temperature stability. Laser cladding processes have high processing costs, limited forming area, and are prone to residual stress and microcracks. Cold spray coatings lack density and have weak mechanical properties. Furthermore, nickel-aluminum coatings prepared by single processes generally have limited high-temperature oxidation resistance and poor thermal shock stability, poor thermal expansion matching between the coating and the substrate, and are prone to delamination failure under long-term high and low temperature alternating conditions. At the same time, low-cost, high-performance integrated preparation technologies are still relatively scarce. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a corrosion-resistant nickel-aluminum intermetallic compound coating and its preparation method.

[0005] The technical solution of the present invention is: a corrosion-resistant nickel-aluminum intermetallic compound coating, wherein the coating is composed of a single-phase Ni3Al intermetallic compound and Al2O3 dispersed particles accounting for 1% of the total mass of the single-phase Ni3Al intermetallic compound.

[0006] Preferably, the coating thickness is 80~350μm.

[0007] Preferably, the coating has a density of ≥98.2% and an interfacial bonding strength with the carbon steel substrate of ≥72MPa; the coating has a corrosion resistance time of ≥1800h in 3.5wt% NaCl neutral salt spray.

[0008] Secondly, the present invention provides a method for preparing a corrosion-resistant nickel-aluminum intermetallic compound coating, comprising: S1: Place Ni powder with a particle size of 30-60μm and Al powder with a particle size of 40-50μm into a vacuum drying oven and vacuum dry at 60℃~80℃ for 2~4 hours. S2: Dry 30-60μm Ni powder and 40-50μm Al powder are loaded into a stainless steel ball mill jar in a high-purity argon glove box, along with stainless steel grinding balls of different diameters. Anhydrous ethanol is added as a process control agent at 1%~2% of the total mass of Ni and Al powders, and the ball mill jar is tightly sealed under an argon atmosphere. The sealed ball mill jar is then installed on a planetary high-energy ball mill, with the speed set to 200~300rpm. The ball mill is effectively milled for 2~6 hours using an intermittent operation mode of grinding for 30 minutes and stopping for cooling for 15 minutes. After passivation and sieving, Ni@Al coated powder is obtained. S3: Place the Ni@Al coated powder in a vacuum oven and dry it under vacuum at 100℃~120℃ for 2 hours to obtain dried Ni@Al coated powder; S4: The dried Ni@Al coated powder is loaded into a high-purity quartz boat or alumina crucible and placed in a vacuum tube furnace or atmosphere-protected furnace for heat treatment using a two-stage heating strategy. In the first stage, the temperature is increased to 500-550℃ at a rate of 2-5℃ / min and held for 2-4 hours to generate an aluminum-rich transition phase and construct a diffusion barrier layer. In the second stage, the temperature is increased to 850~950℃ at a rate of 5℃ / min and held for 4~8 hours. After furnace cooling, the single-phase Ni3Al intermetallic compound was obtained by crushing and screening. S5: Add 1% by mass of Al2O3 powder of the single-phase Ni3Al intermetallic compound to the single-phase Ni3Al intermetallic compound, mix evenly to obtain a mixed powder; S6: Spray the prepared mixed powder onto the surface of the substrate material. After spraying, place the substrate material with the mixed coating into a heat treatment furnace and introduce argon gas as an inert protective atmosphere. Under the protection of argon gas, set the furnace temperature to 490℃-510℃ and hold for 8~12 hours to obtain the intermetallic compound coating.

[0009] Preferably, in step S1, the mass ratio of Ni powder with a particle size of 30-60 μm to Al powder with a particle size of 40-50 μm is 3:1.

[0010] Preferably, in step S2, the mass ratio of Ni powder and Al powder to stainless steel grinding balls is 10:1-15:1; the diameter of the stainless steel grinding balls is 5mm-10mm.

[0011] Preferably, in step S2, after ball milling, the ball milling jar is placed back into the argon glove box, allowed to cool to room temperature before being opened, and then slowly passivated in an argon atmosphere containing trace amounts of oxygen for 2-5 hours, before being sieved through a 250-500 mesh standard sieve to remove agglomerated particles.

[0012] Preferably, in step S4, the vacuum inside the furnace is ≤10 throughout the heat treatment process. -3 Alternatively, continuously introduce 99.99% high-purity flowing argon gas, with an outlet temperature ≤80℃.

[0013] Preferably, in step S4, furnace cooling is carried out under continuous argon protection. After cooling, the cake powder with a slight sintering neck is placed in a low-energy ball mill or mortar and lightly ground and dispersed. It is then sieved through a standard sieve of 200-300 mesh to obtain a single-phase Ni3Al intermetallic compound.

[0014] Preferably, in step S6, during the spraying process, the distance between the nozzle and the substrate surface is maintained at 10-20 mm, the nozzle moving speed is 300-500 mm / min, the spraying angle is 90°, the powder supply rate is controlled at 0.5-1 g / s, the spraying gas temperature and the air temperature are 500℃-600℃ and 200-600℃ respectively, and the working air pressure is maintained at 1~1.5 MPa.

[0015] Preferably, in step S6, the base material is either 45# carbon steel or Q235 carbon steel.

[0016] The beneficial effects of this invention are as follows: 1. This invention employs a high-purity argon gas-sealed environment and anhydrous ethanol as process control agents, along with an intermittent ball milling process. The mechanical extrusion of the milling balls ensures that soft aluminum uniformly coats nickel particles, avoiding defects such as nickel-aluminum powder mixing, localized aluminum enrichment, or aluminum deficiency in conventional powder mixing processes. Ethanol effectively inhibits cold welding and agglomeration of the powder. Combined with gradient sieving, the core-shell coating integrity is ≥95%. Based on a regular core-shell structure, this invention achieves a final powder with a total impurity phase content of <3wt% and a single Ni3Al purity >97%. 2. In this invention, the aluminum-rich transition phase is preferentially generated in the low-temperature pre-diffusion section of 500~550℃, which consumes free elemental aluminum in advance and avoids the powder melting and agglomeration caused by excessively rapid heating and SHS self-propagation high-temperature synthesis. The slow diffusion in the high-temperature section realizes the transition phase to Ni3Al steady-state phase transformation. The step-by-step diffusion reaction weakens the composition voids caused by the Kirkendall effect. The powder particles have regular morphology, are loose and easy to sieve, and do not require additional crushing and refining. 3. This invention introduces 1 wt% ultrafine Al2O3 ceramic particles into the Ni3Al matrix. The Al2O3 disperses and pins the Ni3 grain boundaries, inhibiting the formation of through pores due to uneven plastic deformation of particles during the spraying process. Combined with precisely controlled low-pressure cold spraying process parameters, the finished coating has a density ≥98.2% and a porosity <1.8%, completely eliminating through corrosion channels and blocking the path of corrosive media to penetrate inward from the microstructure. 4. The cold spraying process of this invention has no high-temperature heat input to the substrate, avoiding the problems of coarse substrate grains, component deformation, and thermal stress cracking caused by the high-temperature flame of seepage and hot spraying; the low-temperature tempering at 490~510℃ after spraying promotes the interdiffusion of trace elements at the coating-substrate interface, forming a metallurgical transition layer, and the coating interface bonding strength is ≥72MPa. It is not easy to peel off or delaminate under alternating hot and cold conditions. 5. The hard Al2O3 particles of this invention are uniformly dispersed and embedded in the Ni3Al grain boundaries, which plays a role in dispersion strengthening and wear resistance reinforcement. The microhardness of the coating is increased by more than 25% compared with the pure Ni3Al coating, and the friction and wear volume is reduced by 30%. The intrinsic thermal expansion coefficient of Ni3Al has a high degree of matching with carbon steel. With the help of the dispersed phase to release thermal stress, there is no cracking or peeling of the coating after 150 repeated hot and cold shocks at 650°C and room temperature. 6. The coating of this invention has a corrosion resistance life of ≥1800h in a 3.5wt% neutral NaCl salt spray environment, while conventional arc-sprayed nickel-aluminum coatings show pitting corrosion and perforation of the substrate in only 350~450h. In electrochemical testing, the coating's self-corrosion potential shifts positively by >250mV and the corrosion current density is reduced to 1 / 12 of that of the conventional coating. After continuous oxidation in air at 650℃ for 100 hours, the coating's oxidation weight gain is ≤0.32mg / cm². During high-temperature service, a continuous and dense protective α-Al2O3 oxide film spontaneously forms on the coating surface, blocking O2 from diffusing inward. Compared with conventional nickel-aluminum coatings, the high-temperature oxidation resistance life is increased by more than 3 times. Attached Figure Description

[0017] Figure 1 This is a cross-sectional SEM image of the Ni3Al intermetallic compound coating prepared in Example 1 of the present invention; Figure 2 This is a schematic diagram of the polarization curve of the Ni3Al intermetallic compound coating prepared in Example 1 of the present invention; Figure 3 This is an impedance side view of the Ni3Al intermetallic compound coating prepared in Example 2 of the present invention; Figure 4 This is a macroscopic comparison image of the Ni3Al intermetallic compound coating prepared in Example 2 of the present invention before and after corrosion. Figure 5 This is an impedance side view of the Ni3Al intermetallic compound coating prepared in Example 3 of the present invention; Figure 6 This is a microscopic comparison image of the Ni3Al intermetallic compound coating prepared in Example 3 of the present invention before and after corrosion. Detailed Implementation

[0018] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings: Example 1 This embodiment provides a method for preparing a corrosion-resistant nickel-aluminum intermetallic compound coating, comprising: S1: Ni powder with a particle size of 30μm and Al powder with a particle size of 40μm are placed in a vacuum drying oven and vacuum dried at 60℃ for 2 hours to fully remove the adsorbed moisture on the powder surface and prevent subsequent agglomeration. The mass ratio of 30μm Ni powder to 40μm Al powder is 3:1. S2: Dry 30μm Ni powder and 40μm Al powder are loaded into a stainless steel ball mill jar in a high-purity argon glove box, and stainless steel grinding balls of different diameters are loaded. The mass ratio of powder to stainless steel grinding balls is 10:1; the diameter of the stainless steel grinding balls is selected as 10mm and 5mm. Then, anhydrous ethanol was added at a ratio of 1:1 (total mass of Ni powder and Al powder) as a process control agent to reduce surface energy and prevent excessive cold welding and agglomeration of the powder; and the ball mill jar was tightly sealed under an argon atmosphere. The sealed grinding jar is installed on a planetary high-energy ball mill. The speed is set to 200 rpm. The ball mill is effectively milled for 2 hours by using an intermittent operation mode of grinding for 30 minutes in the forward direction and stopping to cool for 15 minutes. The impact and extrusion of the grinding balls cause the softer Al powder to undergo plastic deformation, and then it is uniformly coated on the surface of the harder Ni powder through cold welding. After ball milling, the milling jar is placed back into the argon glove box and allowed to cool to room temperature before being opened to cope with the possible pressure inside the jar and the high activity of the powder. If the powder needs to be processed in air later, it is first slowly passivated in an argon atmosphere containing trace amounts of oxygen for 2 hours to form a dense alumina protective film on its surface to prevent spontaneous combustion. Then, the collected powder is sieved using a standard sieve with a mesh size of 250 to remove a small amount of large-particle cold-welded agglomerates, thus obtaining Ni@Al coated powder. S3: Place the Ni@Al coated powder in a vacuum oven and vacuum dry it at 100°C for 2 hours to fully remove the moisture adsorbed on the powder surface and evaporate the residual ethanol from the process control agent added during ball milling, so as to prevent contamination of the furnace body or carbonization of the powder during subsequent high-temperature treatment, and obtain dried Ni@Al coated powder. S4: The dried Ni@Al coated powder is loaded into a high-purity quartz boat or alumina crucible and placed in a vacuum tube furnace or atmosphere-protected furnace for heat treatment using a two-stage heating strategy. In the first stage, the temperature is increased to 500℃ at a rate of 2℃ / min and held for 2 hours to generate an aluminum-rich transition phase, construct a diffusion barrier layer, and consume free elemental aluminum in advance. In the second stage, the temperature is increased to 850℃ at 5℃ / min and held for 4 hours. During this stage, the transition phase generated in the early stage undergoes deep diffusion and phase transformation recombination with the unreacted Ni core inside, which eventually makes the particle composition more uniform and completely transforms into a single-phase Ni3Al intermetallic compound. After furnace cooling, the powder was crushed and sieved to obtain a single-phase Ni3Al intermetallic compound. The powder was cooled in the furnace under continuous argon protection, and removed from the furnace only after the temperature dropped below 80°C to prevent instantaneous oxidation or spontaneous combustion upon contact with air at high temperatures. After removal, the cake powder with a slight sintering neck was lightly ground and dispersed in a low-energy ball mill or mortar. Finally, it was sieved through a 200-mesh standard sieve to obtain the single-phase Ni3Al intermetallic compound. S5: Add 1% by mass of Al2O3 powder of the single-phase Ni3Al intermetallic compound to the single-phase Ni3Al intermetallic compound, mix evenly to obtain a mixed powder; S6: Spray the prepared mixed powder onto the surface of the substrate material. During the spraying process, the distance between the nozzle and the substrate surface is maintained at 10 mm, the nozzle moving speed is 300 mm / min, the spraying angle is 90°, the powder supply rate is controlled at 0.5 g / s, the spraying gas temperature and the air temperature are 500℃ and 200℃ respectively, and the working air pressure is maintained at 1 MPa.

[0019] After the spraying is completed, the substrate material with the mixed coating is placed in a heat treatment furnace and argon gas is introduced as an inert protective atmosphere. Under the protection of argon gas, the furnace temperature is set at 490℃ and held for 8 hours to obtain the intermetallic compound coating.

[0020] like Figure 1 As shown, the coating prepared in this embodiment is dense overall, without through-holes or large pore defects; Ni and Al elements are evenly distributed inside the coating, and the elements between the Fe matrix and the coating are smoothly transitioned, with no obvious gaps or delamination at the interface; fine Al2O3 particles are uniformly dispersed at the Ni3Al grain boundaries, confirming that the core-shell powder preparation and cold spraying and tempering processes achieve a dense structure design.

[0021] like Figure 2 As shown, the coating prepared in this embodiment has a more positive corrosion potential and a corrosion current that is much lower than that of conventional arc-sprayed nickel-aluminum coatings; the corrosion kinetic parameters are superior, and the electrochemical corrosion resistance is significantly better than that of coatings prepared by existing processes.

[0022] Example 2 This embodiment provides a method for preparing a corrosion-resistant nickel-aluminum intermetallic compound coating, comprising: S1: Ni powder with a particle size of 60μm and Al powder with a particle size of 50μm are placed in a vacuum drying oven and vacuum dried at 80℃ for 4 hours to fully remove the adsorbed moisture on the powder surface and prevent subsequent agglomeration. The mass ratio of 60μm Ni powder to 50μm Al powder is 3:1. S2: Dry 60μm Ni powder and 50μm Al powder are loaded into a stainless steel ball mill jar in a high-purity argon glove box, and stainless steel grinding balls of different diameters are loaded. The mass ratio of powder to stainless steel grinding balls is 15:1; the diameter of the stainless steel grinding balls is selected as 10mm and 5mm. Then, anhydrous ethanol was added at a ratio of 1:1 (total mass of Ni powder and Al powder) as a process control agent to reduce surface energy and prevent excessive cold welding and agglomeration of the powder; and the ball mill jar was tightly sealed under an argon atmosphere. The sealed grinding jar is installed on a planetary high-energy ball mill. The speed is set to 300 rpm. The ball mill is effectively milled for 6 hours by using an intermittent operation mode of grinding for 30 minutes in the forward direction and stopping to cool for 15 minutes. The impact and extrusion of the grinding balls cause the softer Al powder to undergo plastic deformation, and then it is uniformly coated on the surface of the harder Ni powder through cold welding. After ball milling, the milling jar is placed back into the argon glove box and allowed to cool to room temperature before being opened. This is to cope with the possible pressure inside the jar and the high activity of the powder. If the powder needs to be processed in air later, it is first slowly passivated in an argon atmosphere containing trace amounts of oxygen for 3 hours to form a dense alumina protective film on its surface to prevent spontaneous combustion. Then, the collected powder is sieved using a 500-mesh standard sieve to remove a small amount of large-particle cold-welded agglomerates, resulting in Ni@Al coated powder. S3: Place the Ni@Al coated powder in a vacuum oven and vacuum dry it at 120°C for 2 hours to fully remove the moisture adsorbed on the powder surface and evaporate the residual ethanol from the process control agent added during ball milling, so as to prevent contamination of the furnace body or carbonization of the powder during subsequent high-temperature treatment, and obtain dried Ni@Al coated powder. S4: The dried Ni@Al coated powder is loaded into a high-purity quartz boat or alumina crucible and placed in a vacuum tube furnace or atmosphere-protected furnace for heat treatment using a two-stage heating strategy. In the first stage, the temperature is increased to 550℃ at 5℃ / min and held for 4 hours to generate an aluminum-rich transition phase, construct a diffusion barrier layer and consume free elemental aluminum in advance. In the second stage, the temperature is increased to 950℃ at 5℃ / min and held for 8 hours. During this stage, the transition phase generated in the early stage undergoes deep diffusion and phase transformation recombination with the unreacted Ni core inside, which eventually makes the particle composition more uniform and completely transforms into a single-phase Ni3Al intermetallic compound. After furnace cooling, the powder was crushed and sieved to obtain a single-phase Ni3Al intermetallic compound. The powder was cooled in the furnace under continuous argon protection, and removed from the furnace only after the temperature dropped below 80°C to prevent instantaneous oxidation or spontaneous combustion upon contact with air at high temperatures. After removal, the cake powder with a slight sintering neck was lightly ground and dispersed in a low-energy ball mill or mortar. Finally, it was sieved through a 300-mesh standard sieve to obtain the single-phase Ni3Al intermetallic compound. S5: Add 1% by mass of Al2O3 powder of the single-phase Ni3Al intermetallic compound to the single-phase Ni3Al intermetallic compound, mix evenly to obtain a mixed powder; S6: Spray the prepared mixed powder onto the surface of the substrate material. During the spraying process, the distance between the nozzle and the substrate surface is maintained at 20 mm, the nozzle moving speed is 500 mm / min, the spraying angle is 90°, the powder supply rate is controlled at 1 g / s, the spraying gas temperature and the air temperature are 600℃ and 600℃ respectively, and the working air pressure is maintained at 1.5 MPa.

[0023] After the spraying is completed, the substrate material with the mixed coating is placed in a heat treatment furnace and argon gas is introduced as an inert protective atmosphere. Under the protection of argon gas, the furnace temperature is set at 510℃ and held for 12 hours to obtain the intermetallic compound coating.

[0024] like Figure 3 As shown, the low-frequency impedance modulus of the coating prepared in this embodiment is much higher than that of the comparative sample, with an impedance value that is 1 to 2 orders of magnitude higher. The dense coating can effectively block the penetration of corrosive media, making it difficult for corrosive media to penetrate the coating and erode the substrate, thus exhibiting excellent shielding and protective performance.

[0025] like Figure 4As shown, the comparative sample exhibited extensive blistering, peeling, and substrate exposure after corrosion; the coating in this embodiment remained intact after corrosion, without peeling or blistering defects. Macroscopically, this demonstrates the coating's long-term resistance to salt spray corrosion and its resistance to failure and detachment during service.

[0026] Example 3 This embodiment provides a method for preparing a corrosion-resistant nickel-aluminum intermetallic compound coating, comprising: S1: Ni powder with a particle size of 50μm and Al powder with a particle size of 45μm are placed in a vacuum drying oven and vacuum dried at 70℃ for 3 hours to fully remove the adsorbed moisture on the powder surface and prevent subsequent agglomeration. The mass ratio of 50μm Ni powder to 45μm Al powder is 3:1. S2: Dry 50μm Ni powder and 45μm Al powder are loaded into a stainless steel ball mill jar in a high-purity argon glove box, and stainless steel grinding balls of different diameters are loaded. The mass ratio of powder to stainless steel grinding balls is 12:1; the diameter of the stainless steel grinding balls is selected as 10mm and 5mm. Then, anhydrous ethanol was added at a ratio of 1:1 (total mass of Ni powder and Al powder) as a process control agent to reduce surface energy and prevent excessive cold welding and agglomeration of the powder; and the ball mill jar was tightly sealed under an argon atmosphere. The sealed grinding jar is installed on a planetary high-energy ball mill. The speed is set to 150 rpm. The ball mill is effectively milled for 4 hours by using an intermittent operation mode of grinding for 30 minutes in the forward direction and stopping to cool for 15 minutes. The impact and extrusion of the grinding balls cause the softer Al powder to undergo plastic deformation, and then it is uniformly coated on the surface of the harder Ni powder through cold welding. After ball milling, the milling jar is placed back into the argon glove box and allowed to cool to room temperature before being opened. This is to cope with the possible pressure inside the jar and the high activity of the powder. If the powder needs to be processed in air later, it is first slowly passivated in an argon atmosphere containing trace amounts of oxygen for 3 hours to form a dense alumina protective film on its surface to prevent spontaneous combustion. Then, the collected powder is sieved using a standard sieve with a mesh size of 450 to remove a small amount of large-particle cold-welded agglomerates, thus obtaining Ni@Al coated powder. S3: Place the Ni@Al coated powder in a vacuum oven and vacuum dry it at 110°C for 2 hours to fully remove the moisture adsorbed on the powder surface and evaporate the residual ethanol from the process control agent added during ball milling, so as to prevent contamination of the furnace body or carbonization of the powder during subsequent high-temperature treatment, and obtain dried Ni@Al coated powder. S4: The dried Ni@Al coated powder is loaded into a high-purity quartz boat or alumina crucible and placed in a vacuum tube furnace or atmosphere-protected furnace for heat treatment using a two-stage heating strategy. In the first stage, the temperature is increased to 520℃ at 3℃ / min and held for 4 hours to generate an aluminum-rich transition phase, construct a diffusion barrier layer and consume free elemental aluminum in advance. In the second stage, the temperature is increased to 900℃ at 5℃ / min and held for 6 hours. During this stage, the transition phase generated in the early stage undergoes deep diffusion and phase transformation recombination with the unreacted Ni core inside, which eventually makes the particle composition more uniform and completely transforms into a single-phase Ni3Al intermetallic compound. After furnace cooling, the powder was crushed and sieved to obtain a single-phase Ni3Al intermetallic compound. The powder was cooled in the furnace under continuous argon protection, and removed from the furnace only after the temperature dropped below 80°C to prevent instantaneous oxidation or spontaneous combustion upon contact with air at high temperatures. After removal, the cake powder with a slight sintering neck was lightly ground and dispersed in a low-energy ball mill or mortar. Finally, it was sieved through a 250-mesh standard sieve to obtain the single-phase Ni3Al intermetallic compound. S5: Add 1% by mass of Al2O3 powder of the single-phase Ni3Al intermetallic compound to the single-phase Ni3Al intermetallic compound, mix evenly to obtain a mixed powder; S6: Spray the prepared mixed powder onto the surface of the substrate material. During the spraying process, the distance between the nozzle and the substrate surface is maintained at 15 mm, the nozzle moving speed is 400 mm / min, the spraying angle is 90°, the powder supply rate is controlled at 0.8 g / s, the spraying gas temperature and the air temperature are 550℃ and 400℃ respectively, and the working air pressure is maintained at 1.2 MPa.

[0027] After the spraying is completed, the substrate material with the mixed coating is placed in a heat treatment furnace and argon gas is introduced as an inert protective atmosphere. Under the protection of argon gas, the furnace temperature is set at 500℃ and held for 10 hours to obtain the intermetallic compound coating.

[0028] like Figure 5 As shown, the coating in this embodiment has a much larger capacitive arc radius than traditional coatings, indicating that the coating interface has a large resistance to charge transfer, making corrosion reactions difficult to occur and resulting in a prominent corrosion barrier effect.

[0029] like Figure 6 As shown, the coating in this embodiment only exhibited sporadic micro-pitting corrosion, and the substrate was not corroded. Conclusion: The microstructure is stable, the dispersed Al2O3 inhibits intergranular corrosion, and the micro-corrosion resistance is significantly improved. Traditional coatings show large-area intergranular corrosion and continuous pitting after corrosion.

[0030] The embodiments and descriptions above are merely illustrative of the principles and preferred embodiments of the present invention. Various changes and modifications may be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A corrosion-resistant nickel-aluminum intermetallic compound coating, characterized in that, The coating is composed of a single-phase Ni3Al intermetallic compound and Al2O3 dispersed particles accounting for 1% of the total mass of the single-phase Ni3Al intermetallic compound.

2. The corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 1, characterized in that: The coating thickness is 80~350μm.

3. The corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 1, characterized in that: The coating has a density of ≥98.2% and an interfacial bonding strength with the carbon steel substrate of ≥72MPa; the coating has a corrosion resistance time of ≥1800h in 3.5wt% NaCl neutral salt spray.

4. A method for preparing a corrosion-resistant nickel-aluminum intermetallic compound coating, characterized in that, include: S1: Place Ni powder with a particle size of 30-60μm and Al powder with a particle size of 40-50μm into a vacuum drying oven and vacuum dry at 60℃~80℃ for 2~4 hours. S2: Dry 30-60μm Ni powder and 40-50μm Al powder are loaded into a stainless steel ball mill jar in a high-purity argon glove box, along with stainless steel grinding balls of different diameters. Anhydrous ethanol is added as a process control agent at 1%~2% of the total mass of Ni and Al powders, and the ball mill jar is tightly sealed under an argon atmosphere. The sealed ball mill jar is then installed on a planetary high-energy ball mill, with the speed set to 200~300rpm. The ball mill is effectively milled for 2~6 hours using an intermittent operation mode of grinding for 30 minutes and stopping for cooling for 15 minutes. After passivation and sieving, Ni@Al coated powder is obtained. S3: Place the Ni@Al coated powder in a vacuum oven and dry it under vacuum at 100℃~120℃ for 2 hours to obtain dried Ni@Al coated powder; S4: The dried Ni@Al coated powder is loaded into a high-purity quartz boat or alumina crucible and placed in a vacuum tube furnace or atmosphere-protected furnace for heat treatment using a two-stage heating strategy. In the first stage, the temperature is increased to 500-550℃ at a rate of 2-5℃ / min and held for 2-4 hours to generate an aluminum-rich transition phase and construct a diffusion barrier layer. In the second stage, the temperature is increased to 850~950℃ at a rate of 5℃ / min and held for 4~8 hours. After furnace cooling, the single-phase Ni3Al intermetallic compound was obtained by crushing and screening. S5: Add 1% by mass of Al2O3 powder of the single-phase Ni3Al intermetallic compound to the single-phase Ni3Al intermetallic compound, mix evenly to obtain a mixed powder; S6: Spray the prepared mixed powder onto the surface of the substrate material. After spraying, place the substrate material with the mixed coating into a heat treatment furnace and introduce argon gas as an inert protective atmosphere. Under the protection of argon gas, set the furnace temperature to 490℃-510℃ and hold for 8~12 hours to obtain the intermetallic compound coating.

5. The method for preparing the corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 4, characterized in that, In step S1, the mass ratio of Ni powder with a particle size of 30-60 μm to Al powder with a particle size of 40-50 μm is 3:

1.

6. The method for preparing the corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 4, characterized in that, In step S2, the mass ratio of Ni powder and Al powder to stainless steel grinding balls is 10:1-15:1; the diameter of the stainless steel grinding balls is 5mm-10mm.

7. The method for preparing the corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 4, characterized in that, In step S2, after ball milling is completed, the ball milling jar is placed back into the argon glove box, allowed to cool to room temperature before being opened, and then slowly passivated in an argon atmosphere containing trace amounts of oxygen for 2-5 hours. Finally, it is sieved through a 250-500 mesh standard sieve to remove agglomerated particles.

8. The method for preparing the corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 4, characterized in that, In step S4, the vacuum inside the furnace is ≤10 throughout the heat treatment process. -3 Pa or continuously introduce 99.99% high-purity flowing argon gas, with an outlet temperature ≤80℃.

9. The method for preparing the corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 4, characterized in that, In step S4, furnace cooling is carried out under continuous argon protection. After cooling, the cake powder with a slight sintering neck is placed in a low-energy ball mill or mortar and lightly ground and dispersed. It is then sieved through a standard sieve of 200-300 mesh to obtain a single-phase Ni3Al intermetallic compound.

10. The method for preparing the corrosion-resistant nickel-aluminum intermetallic compound coating according to claim 4, characterized in that, In step S6, during the spraying process, the distance between the nozzle and the substrate surface is maintained at 10-20mm, the nozzle moving speed is 300-500mm / min, the spraying angle is 90°, the powder supply rate is controlled at 0.5-1g / s, the spraying gas temperature and the air temperature are 500℃-600℃ and 200-600℃ respectively, and the working air pressure is maintained at 1~1.5MPa.